Effects of hormone replacement therapy on C-reactive protein levels in healthy postmenopausal women: comparison between oral and transdermal administration of estrogen - Modena, Maria G; Bursi, Francesca; Fantini, Giuseppe; Cagnacci, Angelo; Carbonieri, Anna; Fortuna, Alessandra; Rossi, Rosario (The American journal of medicine, 2002)
C-reactive protein, an acute phase reactant, is a sensitive marker of inflammation. High plasma levels of C-reactive protein rare associated with an increased risk of myocardial infarction and stroke among apparently health subjects, as well as those at higher risk because of age, smoking, or previous coronary artery disease, and are useful in cardiovascular risk stratification. Moreover, statins have been shown to lower C-reactive protein levels. In contrast, oral hormone replacement therapy appears to increase C-reactive protein levels. However, the effects of different hormonal preparations and their routs of administration are not know. We therefore compared the effects of oral estrogen and transdermal estradiol on C-reactive protein plasma levels in healthy post menopausal women.